ESL Pedagogy in Philippine Colleges: Issues and Reforms through 21st Century Teaching Perspective - Diam Maru P Etcoy; Aeryel Kassandra A. Joverto; Ma. Julia Andrea Paligutan (Universidade Estadual de Alagoas, 2023)
This study explores the teaching and learning of English as a Second Language (ESL) in Philippine colleges and universities, focusing on the issues faced by Filipino professors and students. The researchers examine how 21st-century language methods and pedagogies can improve students' second language competency by citing different approaches teachers can apply in the classroom. The qualitative research design in Interpretative Phenomenological Approach (IPA) aims to identify issues faced by college professors and provide a framework for suggesting pedagogical reform to enhance ESL teaching in the Philippines, particularly in tertiary education. The study focuses on the specificity and coherence of ESL approaches and their connection with 21st-century learning standards. The findings suggest that the existing curriculum needs to increase its distinctiveness, internal coherence, and integration of key 21st-century learning concepts. The degree of application of methods and teaching methods is crucial for the development of students' second language skills. The proposed intervention program aims to develop competent language learners. The literature review will help develop competent language learners. The study concludes with potential implementation issues, recommendations for future design and implementation, and implications for future research.